2019
DOI: 10.1016/j.jss.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Software developer productivity loss due to technical debt—A replication and extension study examining developers’ development work

Abstract: Software companies need to deliver customer value continuously, both from a shortand long-term perspective. However, software development can be impeded by technical debt (TD). Although significant theoretical work has been undertaken to describe the negative effects of TD, little empirical evidence exists on how much wasted time and additional activities TD causes. The study aims to explore the consequences of TD in terms of wastage of development time. This study investigates on which activities this wasted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 43 publications
(69 reference statements)
1
19
0
Order By: Relevance
“…Even though Refactoring slightly out performs the other activities in removing TD, it still introduces substantial amount of TD in a high proportion of cases, and in half of the cases, does not introduce observable changes in the overall amount of TD accumulated in the project. These results are similar to the previous studies (e.g., [13], [16], [27]) that suggest that developers might waste a significant proportion of their time dealing with TD in an inefficient way [13] and that refactoring operations were not found to be effective in removing TD items as Code Smells [27], or even were responsible for introducing bugs [16].…”
Section: A Rq1: the Effect Of Refactoring Bug Fixing And New Develsupporting
confidence: 90%
See 2 more Smart Citations
“…Even though Refactoring slightly out performs the other activities in removing TD, it still introduces substantial amount of TD in a high proportion of cases, and in half of the cases, does not introduce observable changes in the overall amount of TD accumulated in the project. These results are similar to the previous studies (e.g., [13], [16], [27]) that suggest that developers might waste a significant proportion of their time dealing with TD in an inefficient way [13] and that refactoring operations were not found to be effective in removing TD items as Code Smells [27], or even were responsible for introducing bugs [16].…”
Section: A Rq1: the Effect Of Refactoring Bug Fixing And New Develsupporting
confidence: 90%
“…They found that, on average, 25% of development time is spent on managing TD. In [13], the authors investigate the waste of development time with regards to TD management. Their results suggest that developers waste 23% of their time on managing TD (i.e., mainly through refactoring), and developers frequently introduce new TD.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe the remaining reason categories in detail using representative examples in our online appendix 5 to help the reader understand this taxonomy.…”
Section: Rq12 -Satd Rationalementioning
confidence: 99%
“…The applicability of the study was observed through a comparative model based on the experimental arrangement. Besker et al (2019) had discussed a review on the importance of technical debt and time management policies for the effective delivery of the SaaS execution [24]. They had stated that the quality products of the system can be achieved through proper testing strategy.…”
Section: Related Workmentioning
confidence: 99%